Cabbage family affairs: the evolutionary history of Brassicaceae - Franzke, Andreas; Koch, Marcus (Trends in plant science, 2010)
Life without the mustard family (Brassicaceae) would be a world without many crop species and the model organism Arabidopsis (Arabidopsis thaliana) that has revolutionized our knowledge in almost every field of modern plant biology. Despite this importance, research breakthroughs in understanding family-wide evolutionary patterns and processes within this flowering plant family were not achieved until the past few years. In this review, we examine recent outcomes from diverse botanical disciplines (taxonomy, systematics, genomics, paleobotany and other fields) to synthesize for the first time a holistic view on the evolutionary history of the mustard family.
Gesehen am 05.05.2017